Availability of Forage Under Oil Palm Plantation for Cattle Grazing - Purwantari, Nurhayati D; Tiesnamurti, B; Adinata, Y (Indonesian Animal Sciences Society, 2015)
Increasing rate of oil palm plantation in Indonesia since 2008-2011 was 6.92%, that increased from 7,363,703 to 7,873,384 ha. Vegetation grown in the area of oil palm plantation is weed for its main crop. There is potential source of oil palm plantation area for livestock industry. Oil palm-cattle integration system is well known and it has been applied in many oil palm plantations, by the use of waste from oil palm plantation, oil palm by-product, the fronds for feed and feces from cattle as organic fertilizer for the plant. Management of oil palm plantation, including plant maintainance, weeding, providing organic and chemical fertilizer is costly. Grazing system under oil palm would minimize cost problem and oil palm production input can be reduced. One of the systems in oil palm-cattle integration that prospective to be developed is grazing by rotation system. Types of plants under oil palm plantation consist of grasses, legumes, other narrow and broad leaves, some are palatable and some are unpalatable or toxic for cattle. Species of vegetation under oil palm vary among the plantation depending on the age of oil palm plant. Introduction of superior forage into oil palm plantation is promising effort to increase the production and quality of feed. Carrying capacity for cattle varies among the oil palm plantation and depends on vegetation under oil palm plantation and age of oil palm. Studies showed that integration oil palm-livestock by grazing system has been proven economically feasible. Key words: Plantation, oil palm, forage, cattle, grazing